Bedside teaching with case based discussions and flipped classroom in undergraduate medical students - Javed, Kainat; Bin Nasir, Umair; Malik, Zeeshan (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Background: Bedside teaching has remained a foundation of medical education because it fosters learning, teaches appropriate behavior, and can be applied efficiently to promote learning. Case-based learning (CBL) is a new teaching method introduced in the undergraduate medical curriculum that entails preparing students for clinical practice by utilizing real-life clinical scenarios. The study’s objective is to look into the impact of combining case-based learning and bedside teaching on motivation, critical analysis, and cognitive development in final-year MBBS students. Methods: The study participants were final-year medical students placed in a surgery unit for clinical rotations. The research was conducted on 52 students who were placed between August and October 2022. Earlier, an MCQ-based pretest was performed at the start of the rotation. For one hour, students were taught the contents using a case-based learning method, which was shared through flipped classroom before the session, and then they were shown relevant clinical examinations on the bedside. The skills related to the case were performed in front of the teacher by the students, which was then followed by the post-test and questionnaire. Results: This strategy was deemed motivating by 91% of students. It enhances critical thinking, according to 82% of students. 70% of students improved their pre-test and post-test scores by more than 40%. Conclusions: Integration of case-based learning with bedside clinic was correlated with increased motivation of final-year MBBS students and the enhancement of critical thinking skills in students. Keywords: Integration, case-based teaching, bedside teaching, surgery